Correlation between caries activity and salivary microbiota in preschool children - Lin, Xiuyan; Wang, Yuan; Ma, Zhe; Xie, Meng; Liu, Zhuo; Cheng, Jinghui; Tian, Yuzhao; Shi, Hong (Frontiers in Cellular and Infection Microbiology, 2023)
Early childhood caries (ECC) is the most common chronic infectious oral disease in preschool children worldwide. It is closely related to the Caries activity (CA) of children. However, the distribution characteristics of oral saliva microbiomes in children with different CA are largely underexplored. The aim of this study was to investigate the microbial community in saliva of preschool children with different caries activity (CA) and caries status, and to analyze the difference of microbial community in saliva of children with different CA and its correlation with ECC. Subjects were divided into 3 groups based on the Cariostat caries activity test: Group H, high CA (n=30); Group M, medium CA (n = 30); Group L, low CA (n=30). Questionnaire survey was used to explore the related influencing factors of CA. According to the caries status (on the basis of decayed mising filled teeth), these subjects were divided into caries-free group (dmft=0, n=19), caries-low group (0 < dmft ≤ 4, n=27) and caries-high group (dmft > 4, n=44). Microbial profiles of oral saliva were analyzed using 16S rRNA gene sequencing. There was significant differences in the microbial structure (P < 0.05). Scardovia and Selenomonas were the biomarkers of both H group and high caries group. The genus Abiotrophia and Lautropia were the biomarkers of both the L group and the low caries group, while the Lactobacillus and Arthrospira spp. were significantly enriched in the M group. The area under the ROC curve of the combined application of dmft score, age, frequency of sugary beverage intake, and the genus Scardovia, Selenomonas, and Campylobacter in screening children with high CA was 0.842. Moreover, function prediction using the MetaCyc database showed that there were significant differences in 11 metabolic pathways of salivary microbiota among different CA groups. Certain bacteria genera in saliva such as Scardovia and Selenomonas may be helpful in screening children with high CA.